Economic and environmental potential for solar assisted central heating plants in the EU residential sector: Contribution to the 2030 climate and energy EU agenda. (15th February 2019) - Tulus, Victor; Abokersh, Mohamed Hany; Cabeza, Luisa F.; Vallès, Manel; Jiménez, Laureano; Boer, Dieter
Graphical abstract: Highlights: The economic and environmental impact of solar district heating systems is studied. Multi-objective optimization is carried out in a wide range of EU climate zones. A solar fraction above 90% can be achieved for all proposed EU climate zones. High environmental performance is realized in solar district heating systems. The future fuel prices growth supports the solar district heating economically. Abstract: Aligning with the ambitious EU 2030 climate and energy package for cutting the greenhouse emissions and replacing conventional heat sources through the presence of renewable energy share inside efficient district heating fields, central solar heating plants coupled with seasonal storage (CSHPSS) can have a viable contribution to this goal. However, the technical performance variation combined with inadequate financial assessment and insufficient environmental impact data associated with the deployment of those innovative district heating systems represents a big challenge for the broad implementation of CSHPSS in Europe. In this context, our paper presents a comprehensive evaluation for the possibility of integrating CSHPSS in the residential sector in various EU member states through the formulation of a multi-objective optimization framework. This framework comprises the life cycle cost analysis for the economic evaluation and the life cycle assessment for the environmental impact estimation simultaneously. The technical performance is also considered by satisfying both the space heating demand and the domestic hot water services. The methodological framework is applied to a residential neighborhood community of 1120 apartments in various EU climate zones with Madrid, Athens, Berlin, and Helsinki acting as a proxy for the Mediterranean continental, Mediterranean, central European, and Nordic climates, respectively. The optimization results regarding the energy performance show that the CSHPSS can achieve a renewable energy fraction above 90% for the investigated climate zones. At the same time, the environmental assessment shows significant improvement when using the CSHPSS in comparison to a natural gas heating system, in those cases the environmental impact is reduced up to 82.1–86.5%. On the other hand, substantial economic improvement is limited, especially in the Mediterranean climate zone (Athens) due to low heating demands and the prices of the non-renewable resources. There the total economic cost of the CSHPSS plants can increase up to 50.8% compared to a natural gas heating system. However, considering the incremental tendency in natural gas prices all over EU nowadays, the study of future plant costs confirms its favorable long-term economic feasibility.